Presenting the entrepreneurship development model in the national oil refining industry with the approach of environmental damage prevention - Jalal Abdi; Reza Yousefi Saeedabadi; Maryam Taghvaee Yazdi (ارزش آفرینی در مدیریت کسب و کار)
Abstract The aim of this research is to investigate the development model of entrepreneurship in the national oil refining industry with the approach of preventing environmental damage. The current research is applicable in terms of purpose, and descriptive-survey in terms of nature and method. The statistical population of this research includes employees and experts in the national industry of refining petroleum products as many as 951 people, which was considered to be 274 people using Cochran's formula. Sampling was done by cluster random sampling. The collection tool in this research includes a researcher-made questionnaire derived from the qualitative method. The variable of entrepreneurial development includes 4 dimensions of innovation, risk-taking, pioneering and aggressive competition, and the variable of entrepreneurial development includes 3 dimensions of human orientation, environment orientation, and general indifference. The reliability of the research was checked and confirmed using Cronbach's alpha criterion in SPSS software. AMOS software was used to fit the conceptual model of the research. The findings of the research showed that there is a positive and significant effect between the components and dimensions of entrepreneurship development in the national oil refining industry with the approach of preventing environmental damage, and the model has a good fit. Extended Abstract Introduction During the past few years, governments have seriously encouraged entrepreneurship because it benefits the people and the country. People, before starting a business, must have technology capital, necessary facilities to produce goods, suitable workforce, suitable spirit and balanced psychological conditions for success in entrepreneurship. Knowing the needs of entrepreneurs and businesses that need support, it seems that the government is in the best position to determine policy and design programs aimed at encouraging entrepreneurship. The government can cause entrepreneurship through policy implementation in ministries and institutions (Sharifzade et al, 2016). In today's world, the development of entrepreneurship has become a key policy and entrepreneurship has become the most strategic and economic tool of advanced societies. Economic growth and development of countries depends on entrepreneurs and entrepreneurial activities. Therefore, the development of entrepreneurship is necessary to achieve economic development and progress of countries (Zali & Razavi, 2016). Thus, developing entrepreneurship and promoting entrepreneurial culture in the country is a serious economic, social and political necessity (Gholipor et al, 2020). Innovations created by entrepreneurs are strategic factors in economic development and key factors in the business cycle. However, existing evidence shows that growth does not go hand in hand with nature conservation and there is an increasing need for environmental responsibility in entrepreneurship or, in the other word, environmental entrepreneurship (Shirkhani & Karimi, 2018). Therefore, the researcher is trying to answer the question: what is the presentation of the entrepreneurial development model in the national oil refining industry with the approach of preventing environmental damage? Theoretical Framework Entrepreneurship Development The development of entrepreneurship as a macro strategy in a society requires increasing or improving perceptions, tendencies and entrepreneurial behavior at all individual, team, organizational, industry, etc. levels; especially at the national level. In recent years, many countries have put the development of entrepreneurship and entrepreneurial activities on their agenda. But the answer to the question why in some countries, entrepreneurial perceptions, tendencies and behaviors are more than others, is rooted in the important social, cultural and economic factors of society, including national values ​​and culture, government policies and programs, education system, legal institutions, innovation system, financial markets and labor market flexibility (Enayati et al, 2015). Environmental damage The concept of vulnerability is often used in social sciences and there is no agreement on the definition of vulnerability in environmental sciences. Anyway, the concept of environmental vulnerability usually includes biophysical, social and economic aspects. Biophysical factors include geological, geographical and climatic factors; and socio-economic aspects include the inherent resistance of the system to damage, and adaptive capacity (Denner et al, 2015). Zare et al, (2023) investigated the identification of factors affecting the weakening of entrepreneurship in university graduates of Payam Noor universities in Tehran province. The output of the research is to emphasize the strengthening of four variables, including the individual and personal capabilities and qualifications of the graduates, strengthening the educational elements related to the development of entrepreneurship in the university, strengthening the government's support conditions (facilitation, support and encouragement), and finally intervention in the six effective environments on academic entrepreneurship. Sarafzari et al, (2022) investigated the impact of green innovation on green organizational entrepreneurship. The results of this analysis showed that green innovation has a significant effect on green organizational entrepreneurship in the industry, mining and trade organization of Fars province. Green managerial innovation has a significant effect on green organizational entrepreneurship in the industry, mining and trade organization of Fars province. Green product innovation has a significant impact on green organizational entrepreneurship in Fars province industry, mining and trade organization.